2020
DOI: 10.1021/acs.orglett.0c01472
|View full text |Cite
|
Sign up to set email alerts
|

Total Syntheses of Dihydroindole Aspidosperma Alkaloids: Reductive Interrupted Fischer Indolization Followed by Redox Diversification

Abstract: We report a novel reductive interrupted Fischer indolization process for the concise assembly of the 20-oxoaspidospermidine framework. This rapid complexity generating route paves the way toward various dihydroindole Aspidosperma alkaloids with different C-5 side chain redox patterns. The end-game redox modulations were accomplished by modified Wolff–Kishner reaction and photo-Wolff rearrangement, enabling the total synthesis of (−)-aspidospermidine, (−)-limaspermidine, and (+)-17-demeth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 91 publications
0
12
0
Order By: Relevance
“…The end-game redox modulations were performed by using a modied Wolff-Kishner reaction and also a photo-Wolff rearrangement, allowing the total synthesis of (À)-aspidospermidine ( 229), (À)-limaspermidine (232), and also (+)-17-demethoxy-N-acetylcylindrocarine (231). 239 The total synthesis of (À)-aspidospermidine ( 229), (À)-limaspermidine (232), and (+)-17-demethoxy-N-acetylcylindrocarine (231) were Scheme 27 The formal synthesis of (À)-tubifolidine (210).…”
Section: Fischer Indole Synthesismentioning
confidence: 99%
See 3 more Smart Citations
“…The end-game redox modulations were performed by using a modied Wolff-Kishner reaction and also a photo-Wolff rearrangement, allowing the total synthesis of (À)-aspidospermidine ( 229), (À)-limaspermidine (232), and also (+)-17-demethoxy-N-acetylcylindrocarine (231). 239 The total synthesis of (À)-aspidospermidine ( 229), (À)-limaspermidine (232), and (+)-17-demethoxy-N-acetylcylindrocarine (231) were Scheme 27 The formal synthesis of (À)-tubifolidine (210).…”
Section: Fischer Indole Synthesismentioning
confidence: 99%
“…In 2020, Varga et al demonstrated 239 a unique reductive interrupted Fischer indolization method for the short synthesis of the 20-oxoaspidospermidine scaffold. This fast complexity producing pathway covers the route towards different dihydroindole Aspidosperma alkaloids having various C-5 side chain redox patterns.…”
Section: Synthesis Of Indole Moieties In Alkaloids Via ...mentioning
confidence: 99%
See 2 more Smart Citations
“…The concept of “reductive indolization” has been applied in the past for the synthesis of dihydroindole derivatives, [ 11 ] and very recently for Aspidosperma alkaloids. [ 12 ] It can be regarded as the reductive case of an interrupted Fischer indolization, as introduced by Garg and co‐workers. [ 13 ] We now report our efforts to extend the reductive indolization towards hexahydrocarbazole derivatives 10 with a C 3 ‐side chain at the position 4a, thus, accessing the carbon skeleton of compound 4 (Figure 1).…”
Section: Introductionmentioning
confidence: 99%